513 - Lithium monitoring in Old Age Psychiatry – a quality improvement project. (October 2021) - Herridge, E.; Valentine, L.; Cannon, J.; Novac, R.; Marmion, S.; Corcoran, M.; Sweeney, G.; Cryan, M.; McCarthy, G.; Dolan, C.
Abstract : INTRODUCTION: Lithium has a narrow therapeutic index with a risk of toxicity and potential to increase morbidity and mortality, particularly in the elderly with co-morbid illness and polypharmacy. Lithium therapy and monitoring of lithium levels require precision and several guidelines have been issued including recommendations for strict control of lithium levels in the elderly population. RESEARCH OBJECTIVE: We evaluated the effect of implementation of a multifaceted management programme on the compliance with international practice standards for lithium monitoring in patients under the care of Psychiatry of Old Age (POA), Sligo Leitrim Mental Health Services in the North West of Ireland. METHODS: Results from a prior audit performed in February 2020 involving a cohort of 18 patients prescribed lithium under the care of POA were analysed and compared to accepted standards. The guideline used as the benchmark for compliance was the National Institute for Clinical Excellence (NICE) guidelines on the use and monitoring of lithium therapy, as published in 2014. Several deficits were found and therefore a designated Lithium Management Programme was established. A subsequent audit, performed using a simplified audit tool incorporating the NICE guidelines, delivered results which were directly compared to the initial findings and analysed to evaluate the effect of the implemented management programme. PRELIMINARY RESULTS OF THE ONGOING STUDY: In comparison with findings from 2020, there had been a significant improvement in most facets of lithium management and compliance to practice standards. Of particular note was the improvement of biochemical monitoring, side effect screening, polypharmacy surveillance, patient education and interdisciplinary communication. CONCLUSION: The launch of a dedicated Lithium Management Programme with specific features aimed at identifying and addressing poor compliance with monitoring guidelines has led to improved adherence to accepted international practice standards. Our model provides a dynamic, multi-layered system which paves the way for better patient outcomes, timely access to care and furthering education for patients and staff members.